Gold weight implantation as a treatment measure for correction of paralytic lagophthalmos - P Manodh; Pradeep Devadoss; Nishant Kumar (Wolters Kluwer Medknow Publications, 2011)
Ocular complications from facial nerve paralysis can be quite devastating. Facial nerve paralysis results in cosmetic as well as functional problems. Paralysis of the upper eyelids leads to lagophthalmos, which results in incomplete closure of the lid over the cornea, leading to potential complication of corneal ulceration. The management of the affected eye in patients with facial palsy has been improved. Previously, ointment, eye drops, taping, partial or complete tarsorrhaphy was the primary treatment for inability to close the eyelid. Other mechanical techniques for reanimating lid closure are palpebral springs, encircling the upper and lower eyelids with silicone or fascia lata and temporalis muscle transfer. The most popular and widely used static procedure in facial nerve palsy is the upper eyelid gold weight implant. Gold eyelid implants are designed for the gravity assisted treatment of the functional defect of lagophthalmos resulting from facial paralysis. We report a case of a patient with facial paralysis who underwent gold weight implantation of the upper eyelid for correction of paralytic lagophthalmos.